QUALITY OF GOLDEN PAPAYA SOLD IN STREET MARKETS AND SUPERMARKETS IN JOÃO PESSOA - PB : Qualidade de mamão golden comercializado em feiras livres e supermercados de João Pessoa-PB - Pereira da Silva, José Lucas; Brandão Melo de Lima, Handerson; Mendes de Carvalho, Maria Roberta; da Rocha Gomes Ferreira de Almeida, Débora Teresa; Rodrigues Martins, Júlio César; Dantas, Renato Lima (Revista de Ciências da Saúde Nova Esperança, 2024)
Fruit production is a major sector of Brazilian agribusiness and papaya is one of the main fruits sold in the country. The papaya tree is believed to have originated in Central America. The physical characteristics of papaya vary according to the group and variety. There are several ways of selling the fruit, but the main ones are street markets and supermarkets, which follow the trend of modernization in commerce, with a more comfortable environment for customers and the fruit receiving greater care in packaging, handling, and the way it is presented. The aim of this study was to evaluate the quality characteristics of papayas marketed in two locations in the city of João Pessoa-PB, in order to identify possible differences in quality attributes. A completely randomized experimental design was used, with five treatments: fruit from two street markets and fruit from three supermarkets. The following variables were assessed: total fruit mass (g) and pulp weight (g); diameter (cm), length (cm), and color using the Colorimeter app and the phycochemical variable SS/TA ratio. The data on the variables was subjected to analysis of variance (ANOVA) using the F test up to a 5% probability of error level, and then the Scott-Knoot test was carried out at a 5% significance level. With regard to the variables mass, pulp weight, and fruit diameter, the supermarkets had a higher average than the street markets. For the length variable, there was no statistical difference between the treatments. Golden papayas sold in supermarkets in João Pessoa - PB showed superior physical characteristics compared to street markets, especially in terms of fruit mass, pulp weight, and diameter.